Pengembangan Model Pembelajaran Kalkulus Berbantuan Komputer melalui Program Maple di Program Studi Pendidikan Matematika - Parma Parma; Lalu Saparwadi (Jurnal Elemen, 2015)
The purpose of this research is the renewal of learning methods into calculus courses with modules of computer-assisted learning through maple. The products produced in this study is in the form of teaching materials in the form of calculus course lab guide through maple. With the resulting product of this research will be useful theoretically and practically. Theoretically, it is expected to result in the learning principles that can improve the quality of learning calculus, so as to enrich the theory of the existing learning models. Type of research is the development. Learning products developed include: (1). Models and learning strategies; (2). The device in the form of learning, Syllabus, Unit Learning Event, Book Teaching Material Calculus computer-assisted, student worksheet; and (3) test the learning outcomes. Product trials involving calculus course lecturers, heads of university and student mathematics education courses Se-Lombok. The test results were analyzed using descriptive statistics.